2014
DOI: 10.1002/bjs.9621
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of outcome following laparoscopic peritoneal lavage for perforated diverticulitis

Abstract: Elderly patients and those with immunosuppression or severe systemic co-morbidity are at risk of reintervention after laparoscopic lavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…It would be helpful clinically to identify reliable criteria to help surgeons select patients with Hinchey III AD for LL with a high probability of success in controlling sepsis. Previous studies with smaller sample sizes and different outcomes identified ASA grade at least III and chronic use of immunosuppressants as independent predictors of LL failure.…”
Section: Discussionmentioning
confidence: 95%
“…It would be helpful clinically to identify reliable criteria to help surgeons select patients with Hinchey III AD for LL with a high probability of success in controlling sepsis. Previous studies with smaller sample sizes and different outcomes identified ASA grade at least III and chronic use of immunosuppressants as independent predictors of LL failure.…”
Section: Discussionmentioning
confidence: 95%
“…Recent evidence suggests that lavage could be used as a first line in treatment of diverticulitis, if not to cure the disease, at least to prevent a colostomy during subsequent surgery. Also for complications after bowel surgery, lavage is suggested [8][9][10][11][12][13][14][15][16]. RCTs to confirm the beneficial effect of lavage in diverticulitis have been initiated in the Netherlands [23] and in Scandinavia.…”
Section: Discussionmentioning
confidence: 99%
“…Although lavage during laparoscopy is more efficient than during laparotomy [3], its usefulness remains controversial [4][5][6][7]. Over the last years, extensive peritoneal lavage during laparoscopy was reported to be useful for the treatment of complications following colorectal surgery and for diverticulitis [8][9][10][11][12][13][14][15][16]. In animal models, lavage decreases adhesion formation following peritonitis [17].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in all of these trials as well as in the experience of many surgeons, it appears that, when the procedure was a success, it was truly beneficial while when the procedure was a failure, it represented a lost opportunity for the patient. This was well shown by a bi-center French study of 71 patients undergoing laparoscopic lavage for Hinchey III peritonitis [6]. The procedure failed in 11 patients (15%), with an associated mortality of 27%, attesting to the loss of opportunity.…”
mentioning
confidence: 84%